2009
DOI: 10.1245/s10434-009-0695-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Assessment of Sentinel Lymph Nodes After Neoadjuvant Chemotherapy in Patients with Breast Cancer

Abstract: After NAC, FS is an effective method for detecting macrometastasis in the SLN. As in the adjuvant setting, the sensitivity of FS is lower for SLN micro and sub-micrometastasis. Intraoperative FS of the SLN after NAC is indicated to avoid a second surgery because 60% of patients with a positive SLN will have additional positive axillary nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…[29][30][31] Although there was a concern that NAC-induced histological changes of metastases and lymph nodes such as fi brosis, fat necrosis, histiocytic accumulation, and granulation tissue formation may interfere with the detection of metastases, our results were comparable with those obtained in early untreated breast cancer. We compared the results of intraoperative frozen-section (FS) analysis in patients treated with NAC and those not treated with NAC.…”
Section: Intraoperative Assessment Of Sentinel Lymph Nodes After Neoasupporting
confidence: 76%
See 1 more Smart Citation
“…[29][30][31] Although there was a concern that NAC-induced histological changes of metastases and lymph nodes such as fi brosis, fat necrosis, histiocytic accumulation, and granulation tissue formation may interfere with the detection of metastases, our results were comparable with those obtained in early untreated breast cancer. We compared the results of intraoperative frozen-section (FS) analysis in patients treated with NAC and those not treated with NAC.…”
Section: Intraoperative Assessment Of Sentinel Lymph Nodes After Neoasupporting
confidence: 76%
“…Similarly, Rubio et al demonstrated that the sensitivity of FS in an NAC group ranged from 78.5% for micrometastases and isolated tumor cells to 100% for macrometastasis, which were not significantly different from those results obtained in a non-NAC group. 30 Both studies concluded that intraoperative FS analysis of SLN is as accurate for NAC-treated patients as for non-NAC-treated patients and is a clinically acceptable method for detecting SLN metastases to avoid a second operation in the neoadjuvant setting.…”
Section: Intraoperative Assessment Of Sentinel Lymph Nodes After Neoamentioning
confidence: 99%
“…The presence of micrometastasis or ITC in the sentinel lymph node after NAT should be considered as a positive finding making ALND mandatory [49,67]. Posttreatment changes in the removed lymph nodes may be identified if previously positive lymph nodes are removed and assessed.…”
Section: Surgical Lymph Node Stagingmentioning
confidence: 99%
“…When faced with those cases, pathologists may want to consider using frozen sections in addition to TPs to reduce the high false-negative rate associated with the use of TP alone. 20 Knowledge of the grade and histopathologic subtype of the carcinoma before the initiation of therapy could also be helpful. Good communication between pathologists and surgeons is, as always, key.…”
Section: Commentmentioning
confidence: 99%